Extension of the Period for Consent to Increase Quotas Under the Fourteenth General Review of Quotas, the 2008 Reform of Quota and Voice, and the Eleventh General Review of Quotas. (Policy Papers; Policy Paper, 2011)
This paper proposes a six-month extension of the period for consent to increase quotas under the Fourteenth General Review of Quotas. The current deadline is due to expire on December 31, 2011; however, Resolution No. 66-2 provides that the Executive Board may extend the period for consent as it may determine. An extension under the Board of Governor's Resolution No. 66-2 will also extend the periods of consent for quota increases under the 2008 Reform of Quota and Voice (Resolution No. 63-2) and the Eleventh General Review of Quotas (Resolution No. 53-2).